ARCHAEOZOOLOGICAL ANALYSIS OF HORSES FROM THE GASTON WOTA BURIAL GROUND (NORTH OSSETIA-ALANIA, 7th-4th CENTURIES BC) - Spasskaa, Natal'a Nikolaevna; Mosinskij, Aleksandr Pinkusovic (History, Archeology and Ethnography of the Caucasus, 2024)
Representatives of the Koban archaeological culture (12th-3rd centuries BC) inhabited the mountainous areas on both sides of the Greater Caucasus Range, the foothills and plateaus of the southern Stavropol Upland. They led a sedentary lifestyle, engaging in cattle breeding and agriculture. While horse breeding was not a central component of the Koban economy, horses held significant cultural and ritual importance. Despite the abundance of horse remains discovered in Koban archaeological sites, these remains have largely been neglected by dedicated archaeozoological research. This study presents the first comprehensive archaeozoological analysis of horses from the Koban culture, focusing on the Gaston Wota burial ground located in the North Caucasus. The Gaston Wota burial ground yielded the remains of at least 25 horses. These remains were found in various contexts: buried alongside humans, within dedicated burial deposits (36% of individuals each), and in separate sacrificial sites (28%). Notably, the majority of the horses were young animals, with 56% of individuals categorized as under 3.5 years old and 20% falling within the 3.5-4.5 year age range. Sex determination was possible for three individuals, all of whom were identified as stallions. The analysis suggests that horses were likely used for riding purposes starting from the age of 2.5-3 years. In terms of size, the studied Koban horses were primarily medium-sized, with withers heights ranging from 136 to 144 cm. A smaller portion of the sample exhibited shorter heights, falling within the 128-136 cm range. Based on the proportions of limb bones, the horses can be characterized as medium-legged and thin-legged, exhibiting characteristics similar to fast-gaited breeds such as racing or trotting horses. The data obtained from this osteological material does not support the previously held notion, based on artistic depictions, that the Koban culture possessed two distinct horse breeds. However, this conclusion remains preliminary due to the limited size of the sample analyzed.